2021
DOI: 10.1177/13694332211013918
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of isolated bridges with space-bar energy-dissipation devices: Shaking table test

Abstract: The results of the experimental research program realized on a bridge model constructed by using the seismically isolated system upgraded with space-bar devices (USI-SB) are presented in the paper. The installed adaptable system for seismic protection of bridges utilizes double spherical rolling seismic bearings (DSRSB) as seismic isolators, while the qualitative improvement of seismic performances is achieved through the use of novel adjustable multi-directional space-bar energy dissipation (SB-ED) devices. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The extensive innovative and ample original analytical and experimental investigations discussed and used in this paper were performed during the past longer period [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], for the purpose of defining the real potential for practical application of the new HC-RMS-GOSEB system for efficient seismic protection of reinforced concrete and other structures in high rise construction.…”
Section: Results: Conventional and Hc-rms-goseb Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive innovative and ample original analytical and experimental investigations discussed and used in this paper were performed during the past longer period [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], for the purpose of defining the real potential for practical application of the new HC-RMS-GOSEB system for efficient seismic protection of reinforced concrete and other structures in high rise construction.…”
Section: Results: Conventional and Hc-rms-goseb Systemmentioning
confidence: 99%
“…Important technological advances and innovations have been created by the authors based on conducted long-term original analytical and experimental research within several international projects, [1], [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], focused on efficient mitigation of earthquake effects upon engineering structures. Our studies have been planned and realized considering the most recent analytical advances, [3] & [20], and suitable experimental modeling developments, [2], in this specific field.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies suggest that using seismic bearings and dampers leads to seismic retrofit of buildings and bridges (Xiang and Li 2016;Mansouri and Nazari 2017;Zhou and Tan 2018;Luo et al 2019;Kontoni and Farghaly 2019). Recently, studies on the effects of using seismic bearings and dampers indicated that these devices could reduce the seismic response of structures (Cho et al 2020;Hassan and Billah 2020;Cao et al 2020;Zheng et al 2020;Wei et al 2021;Xing et al 2021;Ristic et al 2021;Khedmatgozar Dolati et al 2021;Yuan et al 2021;Chen and Xiong 2022;Marnani et al 2022;Guo et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective solutions for bridges' seismic retro t is using energy dissipation equipment. Extensive studies suggest that energy dissipation devices lead to bridges' seismic retro t [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: -Introductionmentioning
confidence: 99%
“…One of the most effective solutions for bridges' seismic retro t is using energy dissipation equipment. Extensive studies suggest that energy dissipation devices lead to bridges' seismic retro t [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].Studies showed that earthquakes are divided into two groups of near and far fault earthquakes according to the distance of the earthquake recording station from the fault. Each group of earthquakes has speci c characteristics [18][19].…”
mentioning
confidence: 99%